2018
DOI: 10.4149/bll_2018_123
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of BMSCs condition media and methylprednisolone in TGF-β expression and functional recovery after an acute spinal cord injury

Abstract: The purpose of this experimental study is evaluation of the effect of BMSCs Condition Media and Methylprednisolone in TGF-β expression and functional recovery after acute spinal cord injury in adult wistar rat. MATERIAL AND METHODS: After an acute spinal cord injury, MP and BMSC-CM were injected intraperitoneally and the recovery rate was evaluated by BBB and narrow beam test. Real time PCR, H&E staining, cavity formation and stereology was done after 12 weeks post injury. RESULT: There were signifi cant diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…It was noted that the TGF-b1 level in severe patients is significantly lower than that in moderate patients. One possible explanation is that most of the severe patients in this study had undergone the ICU care, treated with corticosteroids (such as methylprednisolone), which inhibit effectively TGF-b1 production [20,21]. In contrast, the effect of corticosteroid therapy on IgA levels is not as obvious [22].…”
Section: Discussionmentioning
confidence: 92%
“…It was noted that the TGF-b1 level in severe patients is significantly lower than that in moderate patients. One possible explanation is that most of the severe patients in this study had undergone the ICU care, treated with corticosteroids (such as methylprednisolone), which inhibit effectively TGF-b1 production [20,21]. In contrast, the effect of corticosteroid therapy on IgA levels is not as obvious [22].…”
Section: Discussionmentioning
confidence: 92%
“…Since our specimens were collected during surgery, patients with TAO underwent routine treatment with methylprednisolone (at a dose of 500-1000 mg, once a day for 3 days) to reduce the intraoperative risk and postoperative inflammatory response, which in turn might lead to the changes in the expression of inflammatory factors. Previous studies have revealed that the expression of collagen, IL-1, IL-2, IL-4, TGF-β, and other inflammatory factors is decreased after using high-doses of methylprednisone for femoral head necrosis, shoulder joint injury, spinal cord injury, Bell's palsy, and other diseases [20][21][22][23][24]. By considering the patient's health and ethical issues, we did not design the TAO surgery group without anti-inflammatory treatment to verify the relationship between HSP47 and inflammatory factors in the retrobulbar adipose tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models with severe [ 140 , 141 ] or moderate [ [142] , [143] , [144] , [145] , [146] ] vertebral contusion/compression or severe transection [ 147 ], MSC-secretome/EVs have been administered intraspinallly [ [140] , [141] , [142] ], intrathecally [ 143 , 145 , 147 ], intramuscularly [ 144 ] or intravenously [ 146 ], showing improved motor function recovery [ 140 , 142 , 143 , 147 ] ( Table 8 ), as also highlighted by a recent meta-analysis [ 148 ]. Other effects observed were enhanced angiogenesis [ 140 ], a tissue protective effect [ 140 , 143 ], an increased axonal regeneration [ 141 , 145 , 146 ], and the attenuation of inflammation [ 143 , 144 , 147 ]. According to the study of Chudickova and colleagues, these effects were common among MSCs and their secretome; however, only secretome treatment resulted in additional enhancements of axonal sprouting and a decrease in the number of reactive astrocytes in the injury site [ 145 ].…”
Section: Msc-secretome and Evs: Pre-clinical And Clinical Safety And ...mentioning
confidence: 99%